The Hikmah Method in Al-Qur'an - Ibrahim Cek Nuh; Usman Haji Thalib (Universitas Islam Negeri Imam Bonjol Padang, 2005)
One of the Islamic Dakwah methods that is used in inviting people to do somethings by implementing